Understanding Chile Pepper Consumers’ Preferences: A Discrete Choice Experiment - Jay Lillywhite; Chadelle Robinson (Agriculture, 2023)
U.S. per-capita chile consumption and foreign imports have increased over the last twenty years while domestic production has fallen. To maintain market share, U.S. chile producers must increase crop revenues and/or decrease production expenses. A better understanding of U.S. consumer preferences relative to chile attributes can provide direction for U.S. chile producers. This paper utilizes a discrete choice experiment within an online survey to gain insights into long-green chile pepper attributes desired by consumers. The results suggest that survey participants prefer fresh long-green chile produced in the United States. Participants also preferred milder long-green chile and value quality inspections. Organic production was preferred to hydroponically produced long-green chile, but a statistical difference between organic and other production practices was not observed. Understanding these preferences may allow producers to better position themselves to remain competitive in the long-green chile market.